Refrigerated raw milk: microbiological, physical-chemical quality and detection of antibiotic residues (Research, Society and Development, 2022)
The objective was to evaluate the microbiological and physical-chemical quality, in addition to verifying the presence of antibiotic residues in refrigerated raw milk samples collected in four individual and five collective tanks located in rural properties belonging to the municipality of Alegre/ES. The samples were coded, placed in sterilized vials and transported to the Laboratory of Microbiology and Biotechnology of the Federal Institute of Espírito Santo Ifes, Campus de Alegre/ES. Microbiological analyzes were performed for total bacterial count and Staphylococcus aureus; physicochemical; in addition to the detection of residues of antibiotics from the β-lactam and tetracycline groups. The mean values for TBC were between 2.0 x 104 CFU mL-1 and 3.0 x 107 CFU mL-1 and it was found that 44.44% of the samples were in compliance with the legislation. The values of S. aureus were between